2021
DOI: 10.3390/ijerph18063240
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Features Indicating the Recovery of Soil Ecosystem Strongly Affected by Mining and Ore Processing

Abstract: Tailings-derived soils formed from waste materials produced during mineral processing often exhibit extremes of pH, low content of organic matter and limited nutrient availability. The success of site revitalization depends mostly on the ability to maintain natural soil functions. We analyzed technogenic sediments from four selected localities in Slovakia defined as environmental burdens: Slovinky (SLS, SLD), Markušovce (MAS, MAD), Lintich (LIS, LID), Horná Ves (HVS, HVD) in the presented research. None of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Londry and Sherriff (2005) reported a significant correlation between microbial biomass and biodiversity with physicochemical conditions in mine tailing in Manitoba (Canada). Their findings were consistent with data reported by Feketeová et al (2021) investigating the recovery of soil ecosystem at tailings ponds affected by mining in Slovakia. Li et al (2018) on the other hand reported microbial diversity increases and high activities of microorganisms induced by applications of zinc, lead, and sulfidic copper in tailing areas in Australia.…”
Section: Introductionsupporting
confidence: 92%
“…Londry and Sherriff (2005) reported a significant correlation between microbial biomass and biodiversity with physicochemical conditions in mine tailing in Manitoba (Canada). Their findings were consistent with data reported by Feketeová et al (2021) investigating the recovery of soil ecosystem at tailings ponds affected by mining in Slovakia. Li et al (2018) on the other hand reported microbial diversity increases and high activities of microorganisms induced by applications of zinc, lead, and sulfidic copper in tailing areas in Australia.…”
Section: Introductionsupporting
confidence: 92%
“…The highest microbial N was found in sulfur + manure treatment in this study, which is one‐third lower than that Ng (2012) reported for a post‐lignite mining site in east Texas, with a mean of 70 μg C/g. Similarly, we found lower microbial C than Feketeová et al (2021) reported, with a value of 315 μg N/g. During open‐pit mining, the topsoil is stripped and stored for use in the restoration of the site after the activity has ceased.…”
Section: Discussionsupporting
confidence: 75%
“…This correlation is consistent with the results obtained in this study. An interesting approach to the presence of soil microorganisms in polluted/post-industrial areas was presented in the study of Feketeova et al [60]. The quoted authors concluded that, in soils contaminated with heavy metals, microorganisms can utilize available nutrients very efficiently without unnecessary energy losses and without difficulties related to survival.…”
Section: Correlation Between Physicochemical Properties and Culturabl...mentioning
confidence: 99%